Path-integral methods for non-adiabatic reaction rates - Lawrence, J (2020)
This thesis discusses recent progress in the development of path-integral methods for non-adiabatic reaction rates in large-scale atomistic simulations. Electronically non-adiabatic reactions are important in a wide range of phenomena, including electron transfer in DNA, enzymatic oxygenation reactions, and the function of light-emitting diodes. Imaginary-time path integrals provide an ideal way to simulate these complex condensed phase reactions, as they are both linearly scaling and capable of accurately describing zero-point energy and tunnelling.